Characterization of Phosphorylated Proteins Using Mass Spectrometry - Yu, Li-Rong; Veenstra, Timothy D. (Current Protein and Peptide Science, 2021)
Phosphorylation is arguably the most important post-translational modification that occurs within proteins. Phosphorylation is used as a signal to control numerous physiological activities ranging from gene expression to metabolism. Identifying phosphorylation sites within proteins was historically a challenge as it required either radioisotope labeling or the use of phospho-specific antibodies. The advent of mass spectrometry (MS) has had a major impact on the ability to qualitatively and quantitatively characterize phosphorylated proteins. In this article, we describe MS methods for characterizing phosphorylation sites within individual proteins as well as entire proteome samples. The utility of these methods is illustrated in examples that show the information that can be gained using these MS techniques.
Keywords: immobilized metal affinity chromatography (IMAC)